Dataset on the fauna and biology of flesh flies (Diptera: Sarcophagidae) in the region of European Russia - Krčmar, Stjepan; Ruchin, Alexander B.; Esin, Mikhail N.; Esina, Irina G.; Khapugin, Anatoliy A. (Frontiers in Insect Science, 2026)
The dataset presents results from studies of Sarcophagidae conducted in 2008, 2013, 2014, and 2016–2024 in the central part of European Russia (Republic of Mordovia). A total of 2,162 males representing 58 species and 10 genera were reliably identified. The highest species diversity of Sarcophagidae was recorded in the Mordovia State Nature Reserve. For the first time in Russia, a new species — Sarcophaga (Heteronychia) slovaca (Povolný and Slamečková, 1967) — was documented. The highest species diversity of Sarcophagidae was recorded in forest glades and floodplains (39 species each). Sarcophaga (Sarcophaga) variegata (Scopoli, 1763) reached its highest abundance in meadows and was relatively common along forest edges. Sarcophaga (Sarcotachinella) sinuata Meigen, 1826 and Sarcophaga (Mimarhopocnemis) granulata Kramer, 1908 predominated in deciduous forests. Metopia grandii Venturi, 1953 and Metopia argyrocephala (Meigen, 1824) were most abundant in burned forest areas. In terms of collection methods, the greatest number of both specimens and species was obtained using yellow pan traps and Malaise traps.